2017
DOI: 10.1016/j.celrep.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Type VI Secretion System Effectors in Target Cell Lysis and Subsequent Horizontal Gene Transfer

Abstract: Bacteria use type VI secretion systems (T6SSs) to manipulate host cells during pathogenesis or to kill competing bacteria, which, in some cases, increases horizontal gene transfer. These functions largely depend on T6SS regulation, dynamics, and the set of effectors that the system delivers into the target cells. Here, we show that Acinetobacter baylyi ADP1 assembles a highly dynamic T6SS capable of killing and lysing bacterial cells. T6SS function depends on conserved T6SS components as well as Acinetobacter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(151 citation statements)
references
References 62 publications
8
128
0
Order By: Relevance
“…This is also consistent with the observation that the tssA VC -negative strain mostly forms small dynamic sheath spots but is still capable of prey killing, albeit with much lower efficiency than the parental strain. It is therefore possible that certain sheath-tube assemblies evolved to be more prone to contraction and contract either before or right after reaching the opposite side of the cell similarly to what was observed in Acinetobacter baylyi (Ringel et al, 2017). This could be achieved by evolution of less stable baseplate or membrane complex that may trigger sheath contraction before extending excessively and potentially bending and detaching from the cell envelope.…”
Section: Discussionmentioning
confidence: 93%
“…This is also consistent with the observation that the tssA VC -negative strain mostly forms small dynamic sheath spots but is still capable of prey killing, albeit with much lower efficiency than the parental strain. It is therefore possible that certain sheath-tube assemblies evolved to be more prone to contraction and contract either before or right after reaching the opposite side of the cell similarly to what was observed in Acinetobacter baylyi (Ringel et al, 2017). This could be achieved by evolution of less stable baseplate or membrane complex that may trigger sheath contraction before extending excessively and potentially bending and detaching from the cell envelope.…”
Section: Discussionmentioning
confidence: 93%
“…Five tag genes were recognized as being conserved in almost all T6SS-1 clusters. These are tagF, which encodes a post-translational regulator and is also present in some unrelated T6SSs such as the H1-T6SS of P. aeruginosa (Lin et al, 2018;Silverman et al, 2011); tagM, encoding a putative outer membrane-anchored lipoprotein of unknown function (Shalom et al, 2007); tagN, encoding a putative PG-anchoring protein (Aschtgen et al, 2010); tagX, encoding a Sec-dependent membrane-anchored peptidoglycan hydrolase that facilitates T6SS sheath assembly through formation of holes in the peptidoglycan layer (Aubert et al, 2015;Ringel, Hu, & Basler, 2017;Weber et al, 2016); and a previously undescribed gene referred to here as tagY.…”
Section: Comparative Analysis Of the T6ss-1 In Burkholderia And Nonmentioning
confidence: 99%
“…Recent evidence has suggested that bacterial predation by A. baylyi can facilitate the acquisition of resistance determinants and may play a key role in interspecies HGT (22, 23). To test the role of bacterial predation in A. baumannii the ability of A118 to lyse K. pneumoniae , as well as E. coli was assessed by performing killing assays.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several studies reported that members of Enterobacteriaceae family harbor resistance determinants typically associated to Acinetobacter genus, a fact that supports the DNA exchange between these bacteria (1521). Moreover, recent evidence showed that bacterial predation by A. baylyi can cause acquisition of resistance determinants and can be key as a tool for inter-species HGT (22, 23). Our focus of study is the A. baumannii clinical strain A118, which was the first A. baumannii strain that demonstrated natural competence in its planktonic state (24).…”
mentioning
confidence: 99%